POLITICAL COMPETITION IN CENTRAL ASIA AND THE CAUCASUS: OBJECTIVES, MEANS, AND MECHANISMS - ERGASHEV, Bakhodyr (CENTRAL ASIA AND THE CAUCASUS, 2011)
Political competition in the newly independent states as an academic problem has acquired a new dimension under the impact of the recent developments in North Africa and West Asia. A large number of academic writings examine the development of political competition in Japan, India, and Turkey,1 while Central Asia and the Caucasus2 plays an important role in analyzing the same problem in the post-Communist countries. Here I have analyzed the political competition processes underway in the domestic policy of the Central Asian and South Caucasian countries starting in 2009, the year Barack Obama became president of the United States.In 1975, Republican President Gerald Ford (1974-1977) assessed the chances of Western democracies in their rivalry with Marxism (particularly in the regions bordering on Soviet Central Asia and the Transcaucasia) as “military competition must be controlled. Political competition must be restrained.”3Said at the height of détente, four years later this formula lost its meaning when the Soviet Union, after capturing President Amin’s residence by storm, invaded Afghanistan during the Democratic Administration of President Carter (1977-1981). This radically changed the situation in Central Asia along with the approaches to political competition.President Carter and the key figures of his administration (Zbigniew Brzezinski in particular) were very impressed by the book To Build a Castle by Vladimir Bukovsky, a prominent Soviet dissident, published in 1978 and similar works which appeared at approximately the same time.